Effectiveness and safety of multidrug therapy containing clofazimine for paucibacillary leprosy and clarithromycin for rifampicin-resistant leprosy: a systematic review and meta-analysis - Montezuma, Thais; Vernal, Sebastian; Andrade, Elaine Nascimento; Brandão, Jurema Guerrieri; de Oliveira, Gustavo Laine Araújo; Gomes, Ciro Martins (Frontiers in Medicine, 2023)
Introduction The present study aimed to evaluate leprosy cure and relapse rates as primary outcomes related to two additional strategies for leprosy treatment: clofazimine for paucibacillary (PB) leprosy patients and clarithromycin for patients with rifampicin-resistant leprosy. Methods We conducted two systematic reviews (protocols CRD42022308272 and CRD42022308260). We searched the PubMed, EMBASE, Web of Science, Scopus, LILACS, Virtual Health Library and Cochrane Library databases, registers of clinical trial databases and gray literature. We included clinical trials evaluating the addition of clofazimine to PB leprosy treatment and the use of clarithromycin for treating patients with rifampicin-resistant leprosy. Risk of bias (RoB) in randomized clinical trials was assessed by the RoB 2 tool and that in non-randomized clinical trials was assessed by the ROBINS-I tool; and the certainty of the evidence was assessed by the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. A meta-analysis of dichotomous outcomes was performed. Results For clofazimine, four studies were included. Cure and relapse rates were not different with the addition of clofazimine to PB leprosy treatment and demonstrated very low certainty of evidence. For clarithromycin, six studies were included. Considerable heterogeneity resulted from the difference between comparators, and studies showed no difference in the assessed outcomes with the addition of clarithromycin to rifampicin-resistant leprosy treatment. Mild adverse events were reported for both drugs but did not significantly impact treatment. Discussion The effectiveness of both drugs still needs to be determined. Adding clofazimine to PB leprosy treatment may reduce the repercussions of an incorrect operational classification with no apparent relevant side effects. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022308272; https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022308260, identifier: CRD42022308272; CRD42022308260.